CHANGES IN UKRAINE'S AGRICULTURAL TRADE WITH THE EUROPEAN UNION DURING WAR - DUKHNYTSKYI, Bogdan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines current situation about foreign trade in agri-food products between Ukraine and the European Union. Special emphasis is placed on its key indicators after the beginning of free trade zone and full-scale war. Differences between the pre-war period and achievements during the war are highlighted. The unchanged product structure of food supplies from our country to the EU market is showed, with a noticeable increase in its total volumes and diversification of the geography of sales in favor for the states with which transport connections were optimal. As an addition, a general description of agricultural imports to Ukraine from the European Union, its main statistical and analytical characteristics is given. The chronology of the introduction protectionist measures by European countries to various food products of Ukrainian agriculture is given. The conditions and restrictions under which our agricultural exports in 2023 work, especially those introduced by Poland, Hungary and Slovakia, are considered. A comparison of the dynamics of its statistical indicators in different periods of 2023 is made to identify the direct consequences of the restrictions, additionally taking into account the termination of the use of the «grain corridor». At the same time, attention is drawn to the unrestricted flow of food imports from the European Union. Possible challenges and threats that will affect mutual sectoral trade between the parties in the short term is characterized, as well as options for the further development of cooperation. An assessment of the final value of Ukraine's food exports to the EU for 2023 is made, taking into account trends of the 4th quarter in the current year. Proposals and recommendations of a scientific nature are given to optimize bilateral sectoral relations at the current stage of cooperation.
Keywords: reorientation; European Union; ban; agricultural export; risks; perspective